Comprehensive Genetic Analysis of Monokaryon and Dikaryon Populations Provides Insight Into Cross-Breeding of Flammulina filiformis - Li, Hui; Shi, Lei; Tang, Weiqi; Xia, Weiwei; Zhong, Yingli; Xu, Xinyu; Xie, Baogui; Tao, Yongxin (Frontiers in Microbiology, 2022)
Flammulina filiformis, as one of the most popular edible fungi in East Asia, is produced in an industrialized and standardized way. However, its monotonous variety and product convergence have seriously restricted the development of the industry. In this study, 11 cultivated strains and 13 wild strains of F. filiformis were collected from multiple regions of China and Japan and were performed genome sequencing. Together with genome data of six strains previously released, in total 23 dikaryons (formed by two monokaryons mating, can making fruiting body), 35 monokaryons (formed by protoplast-regenerating of dikaryon and isolating) were used for genetic diversity and population structure analysis based on the high-throughput genotyping. Firstly, a set of SNP markers with intrapopulation polymorphism including 849,987 bi-allelic SNPs were developed and basically covered all of 11 chromosomes with a high distribution density of 24.16 SNP markers per kb. The cultivated dikaryotic strains were divided into three subgroups, and their breeding history was made inferences, which is consistent with the available pedigree records. The wild dikaryotic strains were divided into two subgroups and showed varied contributions of genetic components with high genetic diversity. All the investigated dikaryons have a symmetric distribution pattern with their two constituent monokaryons in principal component analysis. Finally, we summarized the pedigree relationship diagram of F. filiformis main strains including six modules, and the genotypes of hybrids can be directly phased by the known parental allele according to it. This study provides a method to distinguish two sets of monokaryon haplotypes, and several valuable genetic resources of wild F. filiformis, and an effective strategy for guiding F. filiformis breeding based on the population structure and pedigree relationship in future.